PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK PADA WAJIB PAJAK PRIBADI PADA KPP PRATAMA MERAUKE - Maghfirah, Nurul (Restitusi : Jurnal Riset Perpajakan, 2023)
Research aims to test tax knowledge, service quality and awareness in increasing taxpayer compliance. The data in this research was obtained from each taxpayer registered at KPP Pratama Merauke. This research method uses quantitative methods and the data analysis method used is multiple regression analysis. This research uses primary data by conducting direct research in the field by giving questionnaires/question sheets to 100 respondents located at KPP Pratama Merauke. The research results show that: partially, the tax knowledge variable has a positive and significant effect on taxpayer compliance, the service quality variable has a positive and significant effect on taxpayer compliance, the awareness variable has a positive and significant effect on taxpayer compliance.